2014
DOI: 10.1021/la5020785
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Analysis of Mixed Micelles of a Viologen Surfactant: Extended to Water-in-Oil (w/o) Microemulsion and Cucurbit[8]uril-Assisted Vesicle Formation

Abstract: A systematic study of the self-assembly process of a viologen-containing surfactant in aqueous medium is reported. Dodecyl-ethyl-viologendibromide (DDEV) is mixed in different proportions with dodecyltrimethylammonium bromide (DTAB), and the physicochemical properties of micellization are evaluated in order to find a suitable combination which does not interfere with the micellar properties of DTAB but introduces the characteristic properties of viologen. In this process, 1% doping of DDEV with DTAB was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 49 publications
(122 reference statements)
3
32
0
Order By: Relevance
“…The DLS distribution of the DHN treated solution showed a slight decrease in the particle size ( Figure S7 of the ESI). [37][38][39][40] The solution binding constant for DHN to MV@CB [8] complex, as reported by Scherman et al, was found to be higher than that of Azo-AA (K a = (5.9 ± 0.5) × 10 5 M -1 ). All these information lead to the conclusion that the vesicle structure remained intact even after the addition of DHN.…”
Section: A Competitive Second Guest Releases the Peptide From The Sursupporting
confidence: 64%
See 2 more Smart Citations
“…The DLS distribution of the DHN treated solution showed a slight decrease in the particle size ( Figure S7 of the ESI). [37][38][39][40] The solution binding constant for DHN to MV@CB [8] complex, as reported by Scherman et al, was found to be higher than that of Azo-AA (K a = (5.9 ± 0.5) × 10 5 M -1 ). All these information lead to the conclusion that the vesicle structure remained intact even after the addition of DHN.…”
Section: A Competitive Second Guest Releases the Peptide From The Sursupporting
confidence: 64%
“…32 Importantly, the ternary complex, Trp-HDEV@CB [8] transformed the solutions into spherical nano-aggregates as seen from the FESEM and TEM images ( Figure 2). [37][38][39][40][41] In order to confirm the formation of vesicles, we have entrapped a water soluble dye, CF, inside these nano-aggregates and followed the release of the encapsulated dye through enhancement of fluorescence intensity. [37][38][39][40][41] In order to confirm the formation of vesicles, we have entrapped a water soluble dye, CF, inside these nano-aggregates and followed the release of the encapsulated dye through enhancement of fluorescence intensity.…”
Section: Aromatic Natural Amino Acids As Second Guests For Hdev@cb[8]mentioning
confidence: 99%
See 1 more Smart Citation
“…On account of their high affinities, CB[n]-mediated host-guest interactions are of great interest in the field of supramolecular chemistry and chemical biology. [25][26][27][28][29][30][31][32] While the ability to exhibit multiple non-covalent interactions, CB [8]-mediated heteroternary and homoternary complexes have been exploited in the construction of supramolecular polymers, 33-36 supramolecular hydrogels, [37][38] supra-amphiphiles [39][40] and other supramolecular functional self-assembled systems [41][42][43][44][45][46] .…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…[15,16]. In spite of extensive studies of micelles and RMs using similar set of surfactant(s) [17][18][19][20], a proper understanding at a molecular level is still in demand. In the presence study, we have investigated the effect of mixing of two surfactants (anionic and nonionic) on the physicochemical characterization of the mixed micellar solutions as well as the corresponding RMs in order to optimize and design their properties.…”
Section: Introductionmentioning
confidence: 99%